Algae in the Savica waterfall, Slovenia - Krivograd-Klemenčič, Aleksandra (Natura Sloveniae, 2004)
In 1998, 1999 and 2000, samples were taken seasonally in the Savica Waterfall in Slovenia. The purpose of the investigation was to establish qualitative species structure and relative abundance of the periphyton. In 1999 and 2000, some physical and chemical parameters were also measured. Altogether, 52 species and subspecies of algae were determined. Most of them belonged to Bacillariophyceae. Phormidium sefchelianum Gomont and Cymbella caespitosa (Kiitz.) Brun, were new species to Slovenia.
Keywords: Algae; Alge; Classification; Ecosystem; Ekosistem; Fresh Water; perifiton; Sava Bohinjka; Sladka voda; Slap Savica; slapovi